2014
DOI: 10.1161/circulationaha.114.008777
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Implicates Translationally Controlled Tumor Protein as a Novel Mediator of Occlusive Vascular Remodeling in Pulmonary Arterial Hypertension

Abstract: Although the genetic basis of PAH is known in some cases, the underlying mechanisms that link loss-of-function mutations in BMPR2 with the development of PAH and its characteristic lung vascular lesions are still unclear. Clinical Perspective on p 2135EC injury and apoptosis are key triggers for the development of PAH. Treatment of rats with a vascular endothelial growth factor receptor antagonist, SU5416, together with a period of chronic hypoxia, 9,10 results in a model of severe, Background-Pulmonary arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 53 publications
3
83
0
Order By: Relevance
“…PIR is an iron-binding protein driven by the antioxidant transcription factor NRF2 that could modulate the proinflammatory effects of nuclear factor-kB (41). Interestingly, none of these transcripts matched proteins identified in blood outgrowth ECs previously studied in patients with heritable PAH, perhaps related to differences in cell type and patient cohort (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PIR is an iron-binding protein driven by the antioxidant transcription factor NRF2 that could modulate the proinflammatory effects of nuclear factor-kB (41). Interestingly, none of these transcripts matched proteins identified in blood outgrowth ECs previously studied in patients with heritable PAH, perhaps related to differences in cell type and patient cohort (15).…”
Section: Discussionmentioning
confidence: 96%
“…Such unbiased approaches to gene expression analysis in PAH have been performed on peripheral blood mononuclear cells (12), whole lung tissue (13), and microdissected vessels (14). A recent study investigated proteomic changes in blood outgrowth ECs from four control subjects and four heritable patients with PAH (15) and another compared metabolomic and transcriptomic changes in PAECs engineered with a BMPR2 mutation (16), but no studies to date have specifically addressed changes in gene expression and the functional significance of those features in PAECs derived from patients with IPAH versus those from control lungs. This opportunity has been made possible through the Pulmonary Hypertension Breakthrough Initiative Network, which collects lung tissue from patients with IPAH and APAH and from unused donor control lungs (see the online supplement).…”
mentioning
confidence: 99%
“…The hereditary form (HPAH) is often caused by mutations in the bone morphogenetic protein receptor type 2 gene (BMPR2). Lavoie et al, through a proteomics screen, comparing HPAH patients with BMPR2 mutations with healthy control subjects, identified TCTP as one of 22 significantly altered proteins (Lavoie et al 2014). They reported that TCTP is markedly up-regulated in remodelled blood vessels of complex lesions in lungs from patients with PAH.…”
Section: Blood Circulationmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is a lethal disease characterized by dysregulated growth and apoptosis resistance of pulmonary vascular ECs [97]. Hereditary PAH (HPAH) is often caused by loss-of-function mutations in the bone morphogenetic protein receptor type 2 gene (BMPR2), which is a gene that mediates survival signaling in ECs.…”
Section: Fortilintctp In Human Diseases and Developmental Abnormalmentioning
confidence: 99%